Transport mechanisms through PE-CVD coatings: influence of temperature, coating properties and defects on permeation of water vapour. (31st January 2017) - Kirchheim, Dennis; Jaritz, Montgomery; Mitschker, Felix; Gebhard, Maximilian; Brochhagen, Markus; Hopmann, Christian; Böke, Marc; Devi, Anjana; Awakowicz, Peter; Dahlmann, Rainer
Abstract: Gas transport mechanisms through plastics are usually described by the temperature-dependent Arrhenius-model and compositions of several plastic layers are represented by the CLT. When it comes to thin films such as plasma-enhanced chemical vapour deposition (PE-CVD) or plasma-enhanced atomic layer deposition (PE-ALD) coatings on substrates of polymeric material, a universal model is lacking. While existing models describe diffusion through defects, these models presume that permeation does not occur by other means of transport mechanisms. This paper correlates the existing transport models with data from water vapour transmission experiments.